2023
DOI: 10.1101/2023.01.03.522544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insights into ion conduction by novel cation channel, TMEM87A, in Golgi apparatus

Abstract: TMEM87 family is evolutionarily conserved eukaryotic transmembrane proteins residing in the Golgi1. TMEM87 members play a role in retrograde transport in Golgi and are also proposed mechanosensitive ion channel implicated in cancer and heart disease2-7. In an accompanying study, TMEM87A is described as a voltage-gated, pH-sensitive, non-selective cation channel whose genetic ablation in mice disrupts Golgi morphology, alters glycosylation and protein trafficking, and impairs hippocampal memory. Despite the piv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…S1B). Additionally, in agreement with recent reports ( 11 , 15 ), we found that cells expressing mouse Elkin1 display prominent leak currents at very positive (>+60 mV) and very negative potentials (<−100 mV) (Fig. 1G and fig.…”
Section: Elkin1 Can Detect Mechanical Forcesupporting
confidence: 94%
See 2 more Smart Citations
“…S1B). Additionally, in agreement with recent reports ( 11 , 15 ), we found that cells expressing mouse Elkin1 display prominent leak currents at very positive (>+60 mV) and very negative potentials (<−100 mV) (Fig. 1G and fig.…”
Section: Elkin1 Can Detect Mechanical Forcesupporting
confidence: 94%
“…Cryo–electron microscopy (cryo-EM) structures of human ELKIN1 recently revealed a monomeric seven-transmembrane protein with an N-terminal extracellular Golgi-dynamics domain fold (GOLD domain) ( 10 ). A second, higher-resolution structure recently identified a cation-conduction pathway through the protein ( 11 ). We overexpressed Elkin1 in human embryonic kidney (HEK) 293T cells lacking PIEZO1 channels (HEK293T Piezo1−/− cells) ( 12 ) and found large indentation-induced mechanically activated currents (MA currents) in a majority of transfected cells (Fig.…”
Section: Elkin1 Can Detect Mechanical Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the GOLD-domain is not necessary for mechanical activation of Elkin1. Elkin1 currents showed a distinctive pharmacological profile, being highly sensitive to the non-specific pore-blocker Gd 3+ Additionally, in agreement with a recent report 14 Since Elkin1 is a mechanically-gated channel with properties similar to Piezo2 channels, we hypothesized that this protein could also be involved in mammalian touch sensation. We generated a CRISPR/Cas9 mediated genomic deletion of the mouse Tmem87a/Elkin1 gene locus spanning sequences coding for transmembrane domains 2-6, that includes the proposed ion conduction pathway (Extended Data Fig.…”
Section: Main Textsupporting
confidence: 91%
“…Cryo-EM structures of human Elkin1 recently revealed a monomeric 7 transmembrane protein with an N-terminal extracellular Golgi-dynamics domain fold (GOLD-domain) 13 . A second higher resolution structure recently identified a cation conduction pathway through the protein 14 . We overexpressed Elkin1 in HEK293T cells lacking Piezo1 channels (HEK293T Piezo1-/cells) 15 and found large pokinginduced mechanically-activated currents (MA-currents) in a majority of transfected cells (Fig.…”
Section: Main Textmentioning
confidence: 99%